1993
DOI: 10.1136/hrt.70.6.568
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital resuscitation in East Sussex: 1981 to 1989.

Abstract: Extended training for ambulance staff increases the likelihood of successful resuscitation from out-of-hospital cardiopulmonary arrest. Though instruction in defibrillation must have the highest priority, full paramedical training can bring appreciable additional benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…In Helsinki (population 516 000) cardiac arrests witnessed by paramedical staff were not reported on,13 and about 7 lives per 100 000 were saved by resuscitation compared with 1.5 per 100 000 in our report when we excluded cardiac arrests witnessed by paramedical staff. Moreover, in Brighton during the 1980s about 8 lives per 100 000 were saved 17. Had these results been replicated over the two years in our three health districts at least three times as many lives as the 55 which we recorded might have been saved.…”
Section: Discussionsupporting
confidence: 49%
“…In Helsinki (population 516 000) cardiac arrests witnessed by paramedical staff were not reported on,13 and about 7 lives per 100 000 were saved by resuscitation compared with 1.5 per 100 000 in our report when we excluded cardiac arrests witnessed by paramedical staff. Moreover, in Brighton during the 1980s about 8 lives per 100 000 were saved 17. Had these results been replicated over the two years in our three health districts at least three times as many lives as the 55 which we recorded might have been saved.…”
Section: Discussionsupporting
confidence: 49%
“…Our overall rate of survival to hospital discharge of 6.1% for all cardiac arrhythmias and 11.7% for ventricular fibrillation is similar to other ambulance services in the United Kingdom,1 9 10 but much less than that of 28.9% in Seattle, USA 11. Paramedic skills of ambulance staff have been shown by Lewis et al to increase the likelihood of successful resuscitation12, but from the perspective of accident and emergency department based research, paramedics did not have a major impact on survival, as Guly has reported in Edinburgh 3…”
Section: Discussionmentioning
confidence: 96%
“…Assuming similar success rates, there would be about 640 survivors in the UK annually, but we previously calculated 12 that there would be three times as many (1920) if success rates would be improved to match those in the most successful overseas centres 8 9 or those in one UK centre during the 1980s. 15 To what extent public access defibrillation will improve matters is controversial, 6 16 but other population based studies 17 18 agree with ours that it can be applicable only to about 20% of out of hospital arrests (although slightly more for younger victims) (table 1) and it depends on what proportion of arrests occur in places where a defibrillator is available. 19 At the time of writing, nearly all of the 700 defibrillators that have been provided under the UK national defibrillator scheme are at main line railway stations and airports.…”
Section: Discussionmentioning
confidence: 60%